An intelligent bridge multi-dimension deflection IoT monitoring system based on laser datum and imaging - Dan Zhao; Huifeng Wang; Hao Du; Haoyi Cheng; Lu Peng; Yaru Liang; He Huang; Yunmeng Li (Journal of Traffic and Transportation Engineering (English ed. Online))
Aiming at the all-weather automatic monitoring of bridge structure health monitoring, an embedded bridge multi-dimensional (horizontal and vertical) deflection monitoring system based on dual laser references is proposed. The controller turns on the laser reference transmitter through instructions to emit the laser reference. The intelligent target system located in the middle of the span will calculate the multi-dimensional deflection and deformation information of the bridge structure according to the laser spot projected on the diffuse optical target, and pass this information through the wireless network communication unit transmits to the cloud platform to realize real-time monitoring of the bridge structure status and other parameters. Through the laboratory platform, it is found that the measurement error of this method is less than 300 μm, and the data update rate is less than 66 ms, which meets the requirements of bridge structural health monitoring. This method solves the problem of low efficiency of artificial bridge deflection monitoring, realizes all-weather online real-time monitoring of bridge deflection detection, and ensures the accuracy and efficiency of the measurement system. Applying this monitoring technology not only significantly improves the efficiency and accuracy of bridge structural health monitoring but also plays a crucial role in ensuring safe bridge operations, extending the service life of bridges, and reducing maintenance costs.